Insufficiency of luteal phase defect an assessment of criteria in patients with endocrine forms of infertility - A. G. Davudova (Акушерство, гинекология и репродукция, 2016)
An Insufficiency of the corpus luteum (LPI) is one of the main causes of endocrine forms of infertility and spontaneous loss of the fetus in early pregnancy. Insufficiency of the corpus luteum, and consequently, defective secretory transformation of the endometrium during the second phase of the menstrual cycle, is a direct consequence of violations of folliculogenesis. A comprehensive assessment of the reproductive system prior to initiating therapy allows to develop algorithm of examination of patients, to choose an individual, pathogenetically substantiated treatment strategy, to select the doses and to avoid the possibility of complications. The object of the study is a comprehensive comparative assessment of the reproductive system of patients with impaired function of the corpus luteum suffering from endocrine forms of infertility and optimization criteria for determining the NLF. Materials and Methods: the study involved 170 women, including the control group. During the study was assessed the state of physical, hormonal profile, as well as ultrasound picture of the state of the reproductive system. Results and Conclusion: LPI is a multifactorial condition. Considering the performance levels of progesterone and estradiol, three forms of insufficient of luteal phase were determined and depending on it, the patients received pathogenetically grounded therapy.